Interaction between ACE I/D and ACTN3 R557X polymorphisms in Polish competitive swimmers - Grenda, A.; Leonska-Duniec, A.; Kaczmarczyk, M.; Ficek, K.; Krol, P.; Cieszczyk, P.; Zmijewski, P. (Journal of Human Kinetics, 2014)
We hypothesized that the ACE ID / ACTN3 R577X genotype combination was associated with sprint and endurance performance. Therefore, the purpose of the present study was to determine the interaction between both ACE ID and ACTN3 R577X polymorphisms and sprint and endurance performance in swimmers. Genomic DNA was extracted from oral epithelial cells using GenElute Mammalian Genomic DNA Miniprep Kit (Sigma, Germany). All samples were genotyped using a real-time poly- merase chain reaction. The ACE I/D and the ACTN3 R577X genotype frequencies met Hardy-Weinberg expectations in both swimmers and controls. When the two swimmer groups, long distance swimmers (LDS) and short distance swimmers (SDS), were compared with control subjects in a single test, a significant association was found only for the ACE polymorphism, but not for ACTN3. Additionally, four ACE/ACTN3 combined genotypes (ID/RX, ID/XX, II/RX and II/XX) were statistically significant for the LDS versus Control comparison, but none for the SDS versus Control comparison. The ACE I/D and the ACTN3 R577X polymorphisms did not show any association with sprint swimming, taken individually or in combination. In spite of numerous previous reports of associations with athletic status or sprint performance in other sports, the ACTN3 R577X polymorphism, in contrast to ACE I/D, was not significantly associated with elite swimming status when considered individually. However, the combined analysis of the two loci suggests that the co-occurrence of the ACE I and ACTN3 X alleles may be beneficial to swimmers who compete in long distance races.